Digital video for the desktop - Pender, Ken (Focal Press, 2013)
Practical introduction to creating and editing high quality video on the desktop. Using examples from a variety of video applications, benefit from a professional's experience, step-by-step, through a series of workshops demonstrating a wide variety of techniques. These include producing short films, multimedia and internet presentations, animated graphics and special effects. The opportunities for the independent videomaker have never been greater - make sure you bring your understanding fully up to date with this invaluable guide. No prior knowledge of the technology is assumed, with explanations provided in an easy to understand manner. Ken Pender provides an overview of the hardware and software needed and describes how to output completed projects to the Internet, CD-ROMs, Zip and Jaz discs and videotape. The following software is covered: · Realtime compression: Codecs · Editing, including transitions and special effects: Adobe Premiere, Ulead MediaStudio, Corel Lumiere · 2D Animation: Corel PHOTO-PAINT, Fractal Design Painter, Power Goo · 3D Animation: Ray Dream Studio, MetaCreations Poser and Bryce 3D · Frame stack editing: Adobe Photoshop, Fractal Design Painter · Still image frame editing: CorelDRAW, Fractal Design Painter · Audio creation, editing and mixing: Cool Edit, Goldwave and Multiquence The accompanying CD-ROM provides sample software for Adobe Premiere 5.0, Cool Edit 96, Goldwave 4.02 and Multiquence 1.02. (For further information on Goldwave and Multiquence, see http://www.goldwave.com; for information on Cool Edit, see http://syntrillium.com.).